Diagnóstico da tuberculose em Pelotas: avaliação dos aspectos geográficos e organizacionais dos serviços de Atenção Primária à Saúde na visão dos profissionais de saúde. - Reis, Simone Pieren dos (2013)
Geographical and organizational aspects related to health services are essential for the diagnosis of tuberculosis, since these can become barriers to user access to the health unit and diagnostic actions, which may cause delay in identification of the case, a worsening of the clinical picture and spread of the disease. The objective of this study was to evaluate the geographic and organizational aspects of primary health care services for people's attention with symptoms of tuberculosis, in the vision of health professionals, in the municipality of Pelotas/RS. This is a quantitative study conducted with 276 health professionals active in 50 primary care units of the study site. The data were collected through the application of a structured questionnaire, developed on the basis of "Primary Care Assessment Tool," adapted for attention to tuberculosis and typed in the statistical package Statistica9.1 of StatSoft. The categorical variables were evaluated through the ratio of occurrence and for variables with Likert Scale was used the average value of all the answers of the professionals interviewed.A range from 1 to 2.5 was rated as unsatisfactory", between 2.51 to 3.5 as "regular", and 3.51 to 5.0 as "satisfactory". It was observed that the demand for services next to users' place of residence, the difficulty to move up to the health service, the hours of operation of the services and the availability of sufficient professionals were evaluated by professionals as satisfactory aspects of health services; the adequate compliance of schedule by professionals and turnover of human resources as unsatisfactory. The use of motorized transport and the delay greater than sixty minutes for obtaining medical consultation were considered as regular. The study pointed out that most of the aspects related to the Organization of services has been assessed as non-satisfactory, demonstrating the need to qualify the people management and the management of health services.